Efectos de correctores de acidez de suelos en el cultivo de soya (Glycine max) en la época seca en la zona de Babahoyo - Barrera Carrasco, Elvis Johny (2016)
SUMMARY This work was carried out in of the Experimental Farm "San Pablo", of the Technical University of Babahoyo, located in Km 7.5 of the road Babahoyo - Montalvo. The objective of this work was to evaluate the effectiveness of acidity correctors in several doss, on the pH levels in a cultivated soil planted with soybean, and to determine its effect on the grain yield. Additionally he was carried out an economic analysis. Six treatments and a control without application were investigated, with four repetitions. The sowing was carried out with the varieties INIAP-308, in parcels of 16 m2. The treatments were distributed at random in a design of complete blocks (BCA). The evaluation of stockings of the treatments was carried out using Tukey to 5 significancia%. During cultivation cycle it was evaluated: height of plants, days to flowering, days to harvest, number of sheaths for plant, weight of 100 grains, yielding hectare, pH, soil and foliar, analysis and economical analysis. The results determined that the applications of Sfera 3 in dose of 300 Kg/ha, it impacts on the pH variations, the growth and development dl soya cultivation, especially facilitating the absorption of nutritious, affecting the yield positively above the witness with ranges of 14 % with relationship to the witness without application and 57 % with relationship to the treatment Biocal.